Aromatic polymers made by reductive polydehalogenation of oligocyclic monomers as conjugated polymers of intrinsic microporosity (C-PIMs). Issue 38 (13th September 2019) - Klein, Patrick; Jötten, Hauke J.; Aitchison, Catherine M.; Clowes, Rob; Preis, Eduard; Cooper, Andrew I.; Sprick, Reiner Sebastian; Scherf, Ullrich
Abstract : Incorporation of tetrabenzohepta- or -pentafulvalene connectors into soluble, aromatic polymers results in significantly different optical spectra and intrinsic microporosity. Abstract : Reductive dehalogenation polycondensation of a series of penta- or hexacyclic, bisgeminal tetrachlorides with dicobalt octacarbonyl leads to the formation of homopolymers and copolymers with very different optical spectra. While the formation of tetrabenzoheptafulvalene connectors introduces efficient conjugation barriers due to their strongly folded structure, linking of 5-membered ring-based pentacyclic building blocks via bifluorenylidene connectors allows for an extended π-conjugation along the main chain. A comparison of homopolymer P57 and copolymer P55/77 indicates a quite different reactivity for dichloromethylene functions if incorporated into 5- or 7-membered rings. Interestingly, all investigated (co)polymers show an intrinsic microporosity in the solid-state (forming so-called Conjugated Polymers of Intrinsic Microporosity C-PIMs) and have S BET values of up to 760 m 2 g −1 for homopolymer P77 . This value is one of the highest reported values to date for C-PIMs.